Cognitive Impairment Induced by Lead Exposure during Lifespan: Mechanisms of Lead Neurotoxicity - Daniela Ramírez Ortega; Dinora F. González Esquivel; Tonali Blanco Ayala; Benjamín Pineda; Saul Gómez Manzo; Jaime Marcial Quino; Paul Carrillo Mora; Verónica Pérez de la Cruz (Toxics, 2021)
Lead (Pb) is considered a strong environmental toxin with human health repercussions. Due to its widespread use and the number of people potentially exposed to different sources of this heavy metal, Pb intoxication is recognized as a public health problem in many countries. Exposure to Pb can occur through ingestion, inhalation, dermal, and transplacental routes. The magnitude of its effects depends on several toxicity conditions: lead speciation, doses, time, and age of exposure, among others. It has been demonstrated that Pb exposure induces stronger effects during early life. The central nervous system is especially vulnerable to Pb toxicity; Pb exposure is linked to cognitive impairment, executive function alterations, abnormal social behavior, and fine motor control perturbations. This review aims to provide a general view of the cognitive consequences associated with Pb exposure during early life as well as during adulthood. Additionally, it describes the neurotoxic mechanisms associated with cognitive impairment induced by Pb, which include neurochemical, molecular, and morphological changes that jointly could have a synergic effect on the cognitive performance.